Inhibition by Selenium Compounds of Catecholamine Secretion Due to Inhibition of Ca2+ Influx in Cultured Bovine Adrenal Chromaffin Cells - Uezono Yasuhito; Toyohira Yumiko; Yanagihara Nobuyuki; Wada Akihiko; Taniyama Kohtaro (Elsevier, 2006)
Abstract.: Selenium is an essential trace metal element, whereas large doses of selenium exert adverse effects to the human body. We examined the effects of selenium compounds, sodium selenite (Na2SeO3) and sodium selenate (Na2SeO4), on catecholamine secretion from cultured bovine adrenal chromaffin cells. Treatment of chromaffin cells with sodium selenite for 72, 48, and 24 h caused decreases in protein and catecholamine contents, in association with cell damage, at concentrations over 30, 300, and 300 µM, respectively. The cells treated with subtoxic conditions (<100 µM, 48 h) of sodium selenite were used for further experiments. Sodium selenite treatment for 48 h inhibited carbachol (CCh)-induced catecholamine secretion in a concentration-dependent and non-competitive manner, while it did not affect high K+- and veratridine-induced catecholamine secretion. Sodium selenite (100 µM) did not affect CCh- and veratridine-induced 22Na+ influx, while the compound inhibited 45Ca2+ influx induced only by CCh, but not high K+ and veratridine. Sodium selenate even at higher concentrations (1000 µM) did not affect any stimulus-induced catecholamine secretion and 45Ca2+ influx. Thus, sodium selenite may specifically exert adverse effects, such as inhibition of physiological stimulus-induced catecholamine secretion from adrenal chromaffin cells due to inhibition of Ca2+ influx. Keywords:: adrenal chromaffin cell, catecholamine secretion, ion flux, sodium selenite, trace metal